ADAMTS13 or Caplacizumab Reduces the Accumulation of Neutrophil Extracellular Traps and Thrombus in Whole Blood of COVID-19 Patients under Flow - Yada, Noritaka; Zhang, Quan; Bignotti, Antonia; Ye, Zhan; Zheng, X. Long (Thrombosis and Haemostasis, 2024)
Background Neutrophil NETosis and neutrophil extracellular traps (NETs) play a critical role in pathogenesis of coronavirus disease 2019 (COVID-19)-associated thrombosis. However, the extents and reserve of NETosis, and potential of thrombus formation under shear in whole blood of patients with COVID-19 are not fully elucidated. Neither has the role of recombinant ADAMTS13 or caplacizumab on the accumulation of NETs and thrombus in COVID-19 patients' whole blood under shear been investigated.Methods Flow cytometry and microfluidic assay, as well as immunoassays, were employed for the study.Results We demonstrated that the percentage of H3Cit + MPO+ neutrophils, indicative of NETosis, was dramatically increased in patients with severe but not critical COVID-19 compared with that in asymptomatic or mild disease controls. Upon stimulation with poly [I:C], a double strain DNA mimicking viral infection, or bacterial shigatoxin-2, the percentage of H3Cit + MPO+ neutrophils was not significantly increased in the whole blood of severe and critical COVID-19 patients compared with that of asymptomatic controls, suggesting the reduction in NETosis reserve in these patients. Microfluidic assay demonstrated that the accumulation of NETs and thrombus was significantly enhanced in the whole blood of severe/critical COVID-19 patients compared with that of asymptomatic controls. Like DNase I, recombinant ADAMTS13 or caplacizumab dramatically reduced the NETs accumulation and thrombus formation under arterial shear.Conclusion Significantly increased neutrophil NETosis, reduced NETosis reserve, and enhanced thrombus formation under arterial shear may play a crucial role in the pathogenesis of COVID-19-associated coagulopathy. Recombinant ADAMTS13 or caplacizumab may be explored for the treatment of COVID-19-associated thrombosis.
Keywords: NETosis; neutrophil extracellular traps; ADAMTS13; von Willebrand factor; SARS-CoV-2; COVID-19; thrombosis